Exploiting impacts of antenna selection and energy harvesting for massive network connectivity - Van Nguyen, Minh-Sang; Do, Dinh-Thuan; Al-Rubaye, Saba; Mumtaz, Shahid; Al-Dulaimi, Anwer; Dobre, Octavia (IEEE, 2021)
As a new energy saving approach for green communications, energy harvesting (EH) could be suitable technique to facilitate massive connections for large number of devices in such networks. The spectrum shortage occurs in huge number of devices which access with small-cell and macro-cell networks. To tackle these challenges, we develop a tractable framework relying on prominent techniques such as non-orthogonal multiple access (NOMA), antenna selection and energy harvesting. In this paper, we aim at practical scenarios of small cell networks by jointly evaluating capable of interference management and EH. We benefit from transmission approaches including full duplex (FD) and bi-directional transmission to improve the main performance system metrics such as outage probability and throughput. Three useful schemes are explored by considering EH and inter-cell interference. We derive the closed-form and asymptotic expressions for system metrics. We then perform extensive simulations with different system configurations to confirm the effectiveness of the proposed small-cell NOMA systems.
Keywords: Small-cell; transmit antenna selection; outage probability; non-orthogonal multiple access